To Study the Gen’z Perception About Product and Taste of Balaji Wafers in Ahmedabad City - Aryan, Patel; Drashti, Goswami; Vidani, Jignesh (Contemporary Journal of Applied Sciences, 2024)
This paper provides an in-depth insight into the consulting services provided by Head Quest HR Solutions LLP, known as one of the best-located HR consulting firms in Ahmedabad. The objective of the study was to explore the diversity of services provided, the technologies used, and their effectiveness in improving organizational performance. The study combines quantitative data from structured customer surveys and qualitative data from semi-structured interviews with key stakeholders, through the application of mixed methods methodology. Despite challenges including measuring long-term impact and aligning recommendations with customer culture, the company has done quite well in providing value-added services. Thus, the study offers suggestions for improving the efficiency and effectiveness of consulting services, besides offering practical insights on best practices in HR consulting